Genetic and pharmacologic inhibition of calcineurin reduces biofilm formation by the pathogenic fungus Trichosporon asahii in an in vivo silkworm infection model - Yasuhiko Matsumoto; Yuta Shimizu; Mei Nakayama; Mai Takizawa; Sanae Kurakado; Takashi Sugita (PLoS ONE, 2026)
Trichosporon asahii is a dimorphic pathogenic fungus that causes catheter-related bloodstream infection in immunocompromised patients with neutropenia. Biofilm formation by T. asahii on the surfaces of medical devices such as catheters is influenced by various host environmental factors. Calcineurin, a protein phosphatase composed of the catalytic subunit Cna1 and the regulatory subunit Cnb1, regulates multiple stress responses and virulence of T. asahii . The role of calcineurin in biofilm formation under host-derived conditions, however, remains unclear. Here, we demonstrated that calcineurin is essential for biofilm formation in vivo by T. asahii . While the cna1 gene- and the cnb1 gene-deficient mutants formed biofilms comparable to those of the parent strain in vitro , it produced significantly less biofilm than the parent strain in the in vivo silkworm infection model. Similarly, tacrolimus, a calcineurin inhibitor, did not inhibit biofilm formation by T. asahii in vitro but markedly suppressed biofilm formation in vivo . Together, these findings suggest that calcineurin plays a crucial role in biofilm formation by T. asahii under host environmental conditions.